Legal status of national minorities on the Ukrainian territory in the 19th century - S. Yu. Ivanov (Bulletin of Kharkiv National University of Internal Affairs)
The peculiarities of the formation and development of legal status of national minorities, who were on Ukrainian territory during the studied period and were engaged in various types of economic activity, as well as the influence of the general imperial and local legislation on certain aspects of the life of national minorities, have been investigated.